2012
DOI: 10.1111/j.1467-8462.2012.00692.x
|View full text |Cite
|
Sign up to set email alerts
|

Industrial Relations Reform: Chasing a Pot of Gold at the End of the Rainbow?

Abstract: This article reviews the economy-wide effects of the Work Choices and Fair Work reforms to Australia's industrial relations system. Outcomes examined are wages growth and earnings inequality, labour market adjustment, labour productivity growth and industrial disputes. Little evidence is found of an effect from the industrial relations reforms made in the 2000s. I argue that this is consistent with the nature of the reforms, being primarily oriented to distributive rather than efficiency goals. I finish by des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The Australian Constitution grants the Commonwealth Parliament power to legislate over the conciliation and arbitration of industrial disputes and historically this power had underpinned the centralized wage bargaining regime in Australia. It is only over the last two decades that a relatively rigid wage structure determined through a set of centrally determined “awards” has given way to bargaining at the enterprise level and the individual level (Borland ; Wooden ). Changes to industrial legislation following the re‐election of a Conservative government in 2004 furthered this process.…”
Section: Literature Surveymentioning
confidence: 99%
“…The Australian Constitution grants the Commonwealth Parliament power to legislate over the conciliation and arbitration of industrial disputes and historically this power had underpinned the centralized wage bargaining regime in Australia. It is only over the last two decades that a relatively rigid wage structure determined through a set of centrally determined “awards” has given way to bargaining at the enterprise level and the individual level (Borland ; Wooden ). Changes to industrial legislation following the re‐election of a Conservative government in 2004 furthered this process.…”
Section: Literature Surveymentioning
confidence: 99%
“…In my talk, I examined five types of aggregate‐level outcomes in the Australian economy and labour market during the 2000s: (i) wage inflation; (ii) the distribution of earnings; (iii) labour productivity; (iv) how the labour market adjusts; and (v) strike activity. From this review, I concluded (Borland , pp. 282–3) that there was:
… little evidence of effects from the Work Choices or Fair Work reforms made to Australia's industrial relations system in the 2000s … [and] the limited effects of reforms in the 2000s can be explained by the nature of those reforms—being primarily oriented to changing the relative bargaining power of employers and employees, rather than to enhancing overall economic performance.
…”
Section: How Should Policy‐makers Respond?mentioning
confidence: 98%
“…One area of policy‐making, which received considerable attention a couple of years ago, then faded, but is beginning to make a comeback, and I am sure will get stronger once the Productivity Commission gets the Terms of Reference for its review on the topic, is industrial relations reform. At the time it was receiving so much attention, I gave a talk where I described industrial relations reform as ‘a pot of gold at the end of the rainbow’ (Borland , p. 269). I think that is still the case and I do not regard industrial relations reform as a major opportunity to reduce the rate of unemployment in Australia.…”
Section: How Should Policy‐makers Respond?mentioning
confidence: 99%
“…The Productivity Commission's inquiry into the workplace relations framework found the system to be functioning effectively overall and recommended that 'repair, not replacement, should be the policy imperative' (Productivity Commission, 2015: 2). Moreover, frequent reform since the early 1990s has created considerable uncertainty and adjustment costs at the workplace, with minimal identified benefits to economic performance in return (Borland, 2012;Giudice, 2014).…”
Section: The 2016 Federal Election and Its Aftermathmentioning
confidence: 99%